Reef ecosystem recovery following the Middle Permian (Capitanian) mass extinction - Wang, Xia (2020)
To find out the future of nowadays reef ecosystem turnover under the environmental stresses such as global warming and ocean acidification, analogue studies from the geologic past are needed. As a critical time of reef ecosystem innovation, the Permian-Triassic transition witnessed the most severe demise of Phanerozoic reef builders, and the establishment of modern style symbiotic relationships within the reef-building organisms. Being the initial stage of this transition, the Middle Permian (Capitanian) mass extinction coursed a reef eclipse in the early Late Permian, which lead to a gap of understanding in the post-extinction Wuchiapingian reef ecosystem, shortly before the radiation of Changhsingian reefs. Here, this thesis presents detailed biostratigraphic, sedimentological, and palaeoecological studies of the Wuchiapingian reef recovery following the Middle Permian (Capitanian) mass extinction, on the only recorded Wuchiapingian reef setting, outcropping in South China at the Tieqiao section. Conodont biostratigraphic zonations were revised from the Early Permian Artinskian to the Late Permian Wuchiapingian in the Tieqiao section. Twenty main and seven subordinate conodont zones are determined at Tieqiao section including two conodont zone below and above the Tieqiao reef complex. The age of Tieqiao reef was constrained as early to middle Wuchiapingian. After constraining the reef age, detailed two-dimensional outcrop mapping combined with lithofacies study were carried out on the Wuchiapingian Tieqiao Section to investigate the reef growth pattern stratigraphically as well as the lateral changes of reef geometry on the outcrop scale. Semi-quantitative studies of the reef-building organisms were used to find out their evolution pattern within the reef recovery. Six reef growth cycles were determined within six transgressive-regressive cycles in the Tieqiao section. The reefs developed within the upper part of each regressive phase and were dominated by different biotas. The timing of initial reef recovery ...